Comparative study of bandwidths in copper delafossites from x-ray emission spectroscopy - WATSON, GRAEME; SCANLON, DAVID (My University, 2009)
The widths of the valence bands in the copper (I) delafossites CuGaO2, CuInO2, and CuScO2 have been measured by O?K-shell x-ray emission spectroscopy and are compared with previous experimental work on CuAlO2 and CuCrO2. In agreement with recent density-functional theory calculations it is found that the bandwidth decreases in the series CuAlO2>CuGaO2>CuInO2>CuScO2. It is shown that states at the top of the valence band are of dominant Cu?3dz2 atomic character but with significant mixing with O?2p states.
PUBLISHED
Keywords: Physical chemistry; Delafossite; XES; DFT; Neuroscience